Heterostructure infrared photodiodes - Rogalski, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
HgCdTe remains the most important material for infrared photodetectors despite numerous attempts to replace it with alternative materials such as closely related mercury alloys (HgZnTe, HgMnTe), Schottky barriers on silicon, SiGe heterojunctions, AlGaAs multiple quantum wells, GaInSb strain layer superlattices, high temperature superconductors and especially two types of thermal detectors: pyroelectric detectors and silicon bolometers. It is interesting, however, that none of these competitors can compete in terms of fundamental properties. In addition, HgCdTe exhibits nearly constant lattice parameter that is of extreme importance for new devices based on complex heterostructures. The development of sophisticated controllable vapor phase epitaxial growth methods, such as MBE and MOCVD, has allowed fabrication almost ideally designed heterojunction photodiodes. Examples of novel devices based on heterostructures operating in long wavelength, middle wavelength and short wavelength spectral ranges are presented.